Cinacalcet Effectively Reduces Parathyroid Hormone Secretion and Gland Volume Regardless of Pretreatment Gland Size in Patients with Secondary Hyperparathyroidism - Komaba, Hirotaka; Nakanishi, Shohei; Fujimori, Akira; Tanaka, Motoko; Shin, Jeongsoo; Shibuya, Koji; Nishioka, Masato; Hasegawa, Hirohito; Kurosawa, Takeshi; Fukagawa, Masafumi (Clinical journal of the American Society of Nephrology, 2010)
Cinacalcet is effective in reducing serum parathyroid hormone (PTH) in patients with secondary hyperparathyroidism. However, it has not been proven whether parathyroid gland size predicts response to therapy and whether cinacalcet is capable of inducing a reduction in parathyroid volume. This 52-week, multicenter, open-label study enrolled hemodialysis patients with moderate to severe secondary hyperparathyroidism (intact PTH >300 pg/ml). Doses of cinacalcet were adjusted between 25 and 100 mg to achieve intact PTH <180 pg/ml. Ultrasonography was performed to measure the parathyroid gland size at baseline, week 26, and week 52. Findings were also compared with those of historical controls. Of the 81 subjects enrolled, 56 had parathyroid glands smaller than 500 mm(3) (group S) and 25 had at least one enlarged gland larger than 500 mm(3) (group L). Treatment with cinacalcet effectively decreased intact PTH by 55% from baseline in group S and by 58% in group L. A slightly greater proportion of patients in group S versus group L achieved an intact PTH <180 pg/ml (46 versus 32%) and a >30% reduction from baseline (88 versus 78%), but this was not statistically significant. Cinacalcet therapy also resulted in a significant reduction in parathyroid gland volume regardless of pretreatment size, which was in sharp contrast to historical controls (n = 87) where parathyroid gland volume progressively increased with traditional therapy alone. Cinacalcet effectively decreases serum PTH levels and concomitantly reduces parathyroid gland volume, even in patients with marked parathyroid hyperplasia.